PERAN CYBER ARMY TERHADAP EKSISTENSI BUDAYA MELAYU RIAU - Yudi Daherman; Tessa Shasrini; Harry Setiawan (Jurusan Ilmu Komunikasi Universitas Andalas, 2020)
the formation of community on campus that is based on religion continues to trigger a debate on social media, The action to defend Islam. Students in Riau province as descendants of Malay tribe or live in Riau, use social media and the language used in social media, imagining that they have a role as people who care about information that causes uproar on social media. Cyber army can maintain their existence as students in Riau by maintaining the Malay culture of Riau. This study aims to determine how much influence the role of the cyber army has on the existence of Riau Malay culture. Through testing the theory of the role of the cyber army and the existence of Malay culture in Riau province, the results showed that from a sample of 208 students who were members of the student activity units at 6 universities, they represented. The result is dominant respondents are of Malay ethnic descent. The effect obtained is that the role of the cyber army affects the existence of Riau Malay culture, it is known by looking at the probability value which is 0.00 less than 0.05. The magnitude of the influence of the role of the cyber army on the existence of Riau Malay culture 23.7%,